Ebsteins Anomaly Corrected by Tissue Valve: Case Report - Sabur, SAMA; Rashid, Z; Fazel, A; Chowdhury, MMG; Zaman, M; Haq, N; Badruddoza, M; Kabir, H; Ali, A; Salam, ABM; Razzak, SK (Cardiovascular Journal, 2011)
Ebstein’s anomaly is a rare form of congenital heart disease with incidence of 1% of all congenital heart diseases. There are two modes of surgical correction of Ebstein’s anomaly: either biventricular repair with or without tricuspid valve replacement, or palliative univentricular repair consisting of bidirectional Glenn shunt or Fontan procedure. We treated a case of severe form of Ebstein’s anomaly with ASD secundum with WPW syndrome. Radiofrequency ablation was done to treat WPW syndrome preoperatively. Celermajer’s index is a prognostic indicator for tricuspid valve repair or replacement. On 04.03.08 tricuspid valve was replaced with 31 mm Carpentier-Edwards bovine pericardial valve under cardiopulmonary bypass. Postoperative period was uneventful. Follow up echo done on 01.06.08 which revealed normally functioning tissue valve found in tricuspid position TR Grade I. So, in conclusion, preoperative evaluation and workout of Celermajer’s index is essential before surgical intervention for decision of tricuspid valve repair or replacement. Last but not the least, any event of arrhythmia should be properly evaluated. Key words: Ebstein’s anomaly, WPW (Wolff- Parkinson-White) Syndrome, Celermajer’s index, Tissue valve. DOI: http://dx.doi.org/10.3329/cardio.v1i1.8213 Cardiovasc. j. 2008; 1(1) : 112-114